The preventive effect of dexmedetomidine on paroxysmal sympathetic hyperactivity in severe traumatic brain injury patients who have undergone surgery: a retrospective study - Tang,Qilin; Wu,Xiang; Weng,Weiji; Li,Hongpeng; Feng,Junfeng; Mao,Qing; Gao,Guoyi; Jiang,Jiyao (PeerJ, 2017)
Background Paroxysmal sympathetic hyperactivity (PSH) results and aggravates in secondary brain injury, which seriously affects the prognosis of severe traumatic brain injury patients. Although several studies have focused on the treatment of PSH, few have concentrated on its prevention. Methods Ninety post-operation (post-op) severe traumatic brain injury (sTBI) patients admitted from October 2014 to April 2016 were chosen to participate in this study. Fifty of the post-op sTBI patients were sedated with dexmedetomidine and were referred as the “dexmedetomidine group” (admitted from May 2015 to April 2016). The other 40 patients (admitted from October 2014 to May 2015) received other sedations and were referred as the “control group.” The two groups were then compared based on their PSH scores and the scores and ratios of those patients who met the criteria of “probable,” “possible” and “unlikely” using the PSH assessment measure (PSH-AM) designed by Baguley et al. (2014). The durations of the neurosurgery intensive care unit (NICU) and hospital stays and the Glasgow outcome scale (GOS) values for the two groups were also compared to evaluate the therapeutic effects and the patients’ prognosis. Results The overall PSH score for the dexmedetomidine group was 5.26 ± 4.66, compared with 8.58 ± 8.09 for the control group. The difference between the two groups’ PSH scores was significant (P = 0.017). The score of the patients who met the criterion of “probable” was 18.33 ± 1.53 in the dexmedetomidine group and 22.63 ± 2.97 in the control group, and the difference was statistically significant (P = 0.045). The ratio of patients who were classified as “unlikely” between the two groups was statistically significant (P = 0.028); that is, 42 (84%) in the dexmedetomidine group and 25 (62.5%) in the control group. The differences in NICU, hospital stays and GOS values between the two groups were not significant. Conclusion Dexmedetomidine has a preventive effect on PSH in sTBI patients who have undergone surgery.
Keywords: Paroxysmal sympathetic hyperactivity; Dexmedetomidine; Traumatic brain injury; Preventive effect; Prognosis